An integrated model for the performance of piston ring pack in internal combustion engines. (September 2018) - Mahmoud, Kamel G; Knaus, Oliver; Parikyan, Tigran; Offner, Guenter; Sklepic, Stjepan
Piston rings are important components in internal combustion engines. Their primary function is to seal dynamically the gap between moving piston and cylinder liner surface in order to prevent the combustion gases from penetrating into the crankcase. The rings also control the oil leakage from the crankcase to the combustion chamber. The performance of the piston ring pack impacts the engine efficiency, durability and emissions. The recognition of the impact of the ring-pack performance on the engine design resulted in a sustained effort of research and development aimed at understanding the operation of the piston ring pack. Most of the published models developed in this field are two-dimensional assuming that the ring and liner are perfect circles for the purpose of modelling the axial and radial dynamics. Although this approach has proved to be useful, there exist a number of asymmetrical characteristics of the power cylinder system that can be crucial to the ring-pack performance and therefore it is considered to be appropriate. In this work, an integrated methodology that handles the complex ring-pack mechanism is presented. The physics of the ring-pack mechanism covers the three-dimensional piston ring dynamics of asymmetric engine cylinder due to bore distortion, the mixed lubrication at ring running face as well as the ring flanks and the interring gas dynamics. The modelling method is verified in two steps. In the first step, the dynamic behaviour of the three-dimensional ring model is verified against a commercial finite element software by comparing the eigenmodes up to a frequency of about 1 kHz. In the second step, the ring-pack modelling approach using three-dimensional ring models is also verified against a commercial ring dynamics program, which is based on the two-dimensional modelling. It is shown that the three-dimensional ring dynamics modelling method has advantages over the two-dimensional modelling approach as it facilitates studying the influence of the non-uniform twist along its circumference (ring winding), the effect of bore distortion on blow-by, ring friction, friction power losses and wear.